Erratum to: Hydrological modelling in the anthroposphere: predicting local runoff in a heavily modified high-alpine catchment - Johannes Wesemann; Mathew Herrnegger; Karsten Schulz (Journal of Mountain Science, 2022)
The article Hydrological modelling in the anthroposphere: predicting local runoff in a heavily modified high-alpine catchment, written by Johannes WESEMANN, Mathew HERRNEGGER and Karsten SCHULZ, was mistakenly originally published without open access. After publication in volume 15, issue 5, page 921-938 this was corrected and the article was made an open access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2018 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License ( http://creativecommons.org/licenses/by/4.0/ ), which permits use, duplication, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The original article has been corrected.